Acrylamide gel electrophoresis of proteins of Neisseria gonorrhoeae as an epidemiological tool. - Noble, R C (1978)
The electrophoresis patterns of gonococcal cell proteins were assessed as an aid to gonococcal epidemiology. Lyophilized gonococci were extracted in heated lauryl sulfate with 2-mercaptoethanol. The solubilized gonococcal cell proteins were subjected to alkaline sodium dodecyl sulfate gel electrophoresis, and the resulting patterns were scanned with a spectrophotometer. The electrophoresis patterns were judged to be alike by superimposition of the gel scans. Gonococci thus compared were also auxotyped and tested for sensitivity to penicillin, ampicillin, tetracycline, and spectinomycin. The electrophoresis patterns were reproducible and not affected by serial subculture of the isolates. Patterns from nongonococcal Neisseria species did not resemble those of gonococci. To test the utility of the electrophoresis patterns, duplicate isolates were made from 12 cultures of Neisseria gonorrhoeae. After randomization and blind coding of the 24 isolates, all were successfully matched by their electrophoresis patterns. Cervical-rectal paired isolates from 45 patients were studied by means of their electrophoresis patterns, auxotypes, and results of antibiotic sensitivity tests. Results indicated that the electrophoresis patterns are useful in characterizing paired isolates of gonococci.